Systematic Literature Review: Dampak Perceraian Orang Tua terhadap Kondisi Psikologis Remaja - Cahyarity, Tiara Indah; Putri, Nia Desna; Dania, Nelza Rahma; Utami, Fella Rizki; Arman, Ega (Lembaga Yasin AlSys, 2025)
Divorce for adolescents is a very painful inner pressure that occurs because in general every child wants to live in an intact family. This study aims to determine the various impacts felt by adolescents after their parents divorce based on a review of previous literature. This study uses a systematic literature review method with inclusion criteria in the form of qualitative research, Indonesian language, publications in 2019-2024, and focuses on the impact of divorce in Indonesia. Data sources were taken from Google Scholar, using the keywords “the impact of parental divorce”. The results showed that parental divorce can have a negative impact on children's psychology. However, the study also found positive impacts such as increased independence, stronger mentality, and more mature decision-making ability. In conclusion, parental divorce has a complex range of impacts on adolescents, both negative and positive.